Trauma and Critical Care for the Senior Medical Student Entering Surgery - Mara Antonoff; Courtney Green; Jonathan D'Cunha (Association of American Medical Colleges, 2014)
Abstract Introduction Skills to aid in the management of trauma patients and critically ill surgical patients in the intensive care setting are important topics that are not uniformly covered in medical schools. Significant recent attention has been directed toward developing preparatory courses to bridge this gap and heighten the readiness of senior medical students as they transition to surgical residency. This resource includes comprehensive materials intended to prepare senior medical students for management of trauma patients and critically ill surgical patients in the intensive care setting. Methods The materials provided were designed for use as part of a preparatory course for fourth-year medical students entering surgical specialties, and include all instructor's blueprints, PowerPoint slides, and handouts for four separate sessions. A multiple-choice knowledge test is also included. This resource may be used by course directors for surgery PGY-1 preparatory classes/bootcamps, for independent study by individuals planning to matriculate into surgical residencies, or as a review source for those already in surgical training. While these materials were designed to meet the needs of new surgical house staff, the contents are easily generalizable to other medical specialties, and would prove useful for any trainee managing hospital inpatients. Results The outcomes from this course have been extensively studied. Through pre- and postcourse surveys, knowledge tests, and technical examinations, we measured confidence and skill acquisition in specific, job-related tasks. In 2010, 62 individuals were studied (22 course graduates, 16 PGY-1 nonparticipant controls at our home institution, and 24 nonparticipant peer controls at outside institutions). We found that course participants demonstrated marked improvement in task-specific confidence in all tasks from course beginning to end as indicated by improved scores on written and technical skill examinations. Further, course participants outperformed peers in all tasks one month into internship, with their performance advantage predictably dissipating into the third month of residency. Discussion Utilizing this resource resulted in objective gains in task-specific confidence and test performance at course conclusion, which, importantly, translated to improved performance upon residency matriculation. These data emphasize the significant impact of these competency-based surgical internship preparation materials in formally preparing senior medical students for the care of surgical inpatients.